Do tax incentives reduce investment quality? - Sebastian Eichfelder; Martin Jacob; Kerstin Schneider (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
This paper examines the effect of tax incentives in the form of bonus depreciation on the quality of investment. Using the expiration of tax incentives via bonus depreciation in East Germany and a representative panel of West German establishments, we show that bonus depreciation significantly lowers the quality of investment. The average quality of investments, measured by the responsiveness of future sales to current investment, reduces by 22.6-34.6%. This adverse effect of tax subsidies is greater for jurisdictions with higher tax rates as well as for large or high-productivity firms. Overall, while increasing investment quantity, as shown by prior literature, tax incentives such as bonus depreciation substantially reduce the quality of investments.
Keywords: G11; H25; H32; M41; 330; bonus depreciation; tax incentive; investment incentive; investment quality